Why did the fish cross the tank? Objectively measuring the value of enrichment for captive fish - Sullivan, Miriam; Lawrence, C.; Blache, D. (2016)
© 2015 Elsevier B.V. There has been very little research into the enrichment preferences of ornamental fish, even though there are billions of fish kept in captivity as pets and research animals. We used preference and motivational testing to compare the value of real and artificial plants to goldfish (n = 20, Carassius auratus). Motivational testing was conducted using a novel approach, requiring goldfish (n = 19) to swim against increasingly strong water currents to access the plants. Goldfish showed a strong preference for planted areas of the tank, spending 90% of their time there compared to just 10% in bare areas (P<. 0.001), but did not discriminate between real and artificial plants (P = 0.48). Using water currents has the potential to be a fast and easy way to measure motivation in fish, although goldfish were easily able to swim against much stronger currents (0.7. m/s) than suggested by earlier research.